Thermodynamic analysis of the Ga-Pb binary system - Manasijević Dragan; Živković Dragana; Živković Živan D. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Thermodynamic properties of binary Ga-Pb alloys were investigated experimentally and analytically. Quantitative differential thermal analysis was used for determination of integral mixing enthalpies for the gallium-reach alloys, at the constant temperature inside the liquid two-phase region. Calculation of gallium activities in the temperature range of 800-1000 K was done using Chou’s calculation model developed for binary systems with miscibility gap existence.